Народы России - Широнина Е. В. (Детская энциклопедия РОСМЭН, 2013)
Экземпляры: Селтинская районная библиотека (к/х) (20140530) / Инвентарный номер: 200721 / Цена: 86 / Авт.знак: Н 28 / ГРНТИ: 00 / ББК: 63.5(2)я2